PENGARUH PRODUK, HARGA, LOKASI DAN PROSES TERHADAP KEPUTUSAN PEMBELIAN PADA ALL NEW TSJ CAFE BANGKINANG - Salis, Muhammad; Henrizal, Henrizal; Dwi Prastio, Muhammad (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This research aims to determine the influence of product, price, location and processsimultaneouslyandpartiallyonpurchasingdecisionsattheAllNewTSJCafeBangkinang City. The population in this study is the entire level of visits to the All NewTSJ Café in 2022, which is known to total 10,822 visits. Determining the sample in thisstudy used the Sovin formula which was obtained by 100 respondents. The researchquestionnaire was published to respondents using an accidental sampling technique.Data analysis was carried out using a multiple linear regression model. Based on theresults of simultaneous hypothesis testing, product, price, location and process have asignificant influence on purchasing decisions. Based on the results of partial hypothesistesting,itshowsthatproduct,price,locationandprocessalsohaveasignificantinfluenceon purchasing decisions. The close relationship between product, price, location andprocess on purchasing decisions is very strong with the contribution of product, price,locationandprocesstopurchasingdecisionsamountingto72.9%.Keywords: Product,Price,Location,ProcessandPurchasingDecisions